Ciencias sociales 7 EGB - MEREGA, Herminia dir. (SANTILLANA, 2000)
CONTENIDO : COLAB.RICCARDINI, S. DE; MORICHETTI, M.; RAMACCIOTTI, K.; ACHA, P.; TATO, M.; RAITER, B.; IPPOLITO, M.; SURIANO, L.; HIRSCHMANN, P.; CELOTTO, I.; CATTARUZZA, A.; CASAIS, M.